Analisis Pendidikan Agama Kristen Keluarga Pada Pola Asuh Orang Tua Kristen - Lasewa, Selvie Kristine; Sangauk, Christy I.P. (JURNAL ILUMINASI, 2025)
The purpose of this study is to provide an understanding and description of how proper teaching of Christian Religious Education in the Family impacts the way Christian parents educate and care for their children in their spiritual and physical growth. This theoretical discussion will discuss Christian Religious Education in the family from a biblical perspective, which will be linked to theoretical studies describing Christian Religious Education in the family and the essence of Christian parenting patterns in educating children within Christian families. The research method used in this study is qualitative. The method used is analytical, with data collection techniques using documents from a literature review to examine and analyze Family Religious Education and Parenting Patterns. Therefore, it can be concluded that Christian families play a significant role in shaping children's character.